DEVELOPING DIGITAL EVIDENCE SYSTEMS AS A TOOL TO COMBAT ORGANIZED CRIME IN THE DIGITAL ENVIRONMENT - Layth Abdul Kadhim Khatam; Ruqayah Kadhim Jasim (American Journals Publishing, 2025)
Research aims to study development system Evidence Digital As a tool Effective in Combat Crimes The organization in the environment Digital, with the focus on Aspects Technology legal Organizational For this The evidence . It focuses Search Firstly on clarification concept Evidence Digital and its characteristics distinctive, In what in that Its nature not Materialism, And multiple Its sources, and its sensitivity For change, addition to Her role bio in Discovery on Crimes The organization And follow network Relations between criminals via outer space Digital. As well . He reviews Search framework Legal Organizational that He specifies How to collection Evidence Digital And its use according to procedures Legal Correct, It includes that Controls Inspection Digital, and authorities Adjustment judicial, and conditions acceptance Evidence before The courts, As well as Challenges Legal Related crimes The passerby For the borders . In addition . to that, It deals Search the components Technology For the system, like tools Analysis criminal Digital, And organized administration The evidence and series possession Digital, and mechanisms save Data and its analysis Using Technologies intelligence artificial and link Data, In what Guarantees speed Discovery Accuracy The investigation concludes Search to that development system Integrated For evidence Digital Enhances from capacity Entities Investigation on a statement Crimes The organization Analysis Her behavior, Presentation Evidence Trusted and midwife For use judicial, as Contributes in Strengthening cooperation between Entities Security and judicial locally Internationally, And makes Confrontation Crimes Digital more effectiveness And comprehensive, And it guarantees Balance between protection the society and rights Individuals .
Keywords: Evidence Digital Crimes Organization, Analysis criminal Digital, Series possession Digital, investigation Digital, Management Evidence Digital Crimes Information technology.